Primary Knee Intra-articular Synovial Sarcoma in Pediatric and Adolescent Patients. (April 2021) - Cao, Qi; Shillingford, Nick; Huh, Winston; VandenBerg, Curtis; Raca, Gordana; Allison, Daniel C.; Wang, Larry; Zhou, Shengmei
Synovial sarcoma (SS) arising within a knee joint is extremely rare, with 10 reported cases in pediatric and adolescent patients in English literature. Its rarity and nonspecific clinical and radiological features pose a diagnostic challenge. We present two cases of primary intra-articular SS of left knee to enhance awareness of this entity. One patient is a 17-year-old male complained of left knee pain and gait abnormality for 9 years. The other one is a 13-year-old female presented with left knee pain for one year. Both cases were clinically diagnosed as benign joint lesion and underwent biopsies. Histological examination, immunohistochemical staining and molecular study confirmed that both patients had primary intra-articular SS, monophasic spindle cell type. Intraarticular SS should be considered as a potential diagnosis with unexplained long-standing knee pain.